POLA ASUH PERMISIF ORANG TUA BAGI ANAK YANG MENGALAMI SPEECH DELAY - Febriana, Reza; Eska Prawisudawati Ulpa; Nugroho Arief Setiawan3 (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Parenting styles play a crucial role in children’s language development; however, in practice, many parents still apply permissive parenting, which may contribute to the occurrence of speech delay. A lack of supervision, clear boundaries, and consistent communication stimulation can hinder the optimal development of children’s language abilities. This study aims to describe permissive parenting styles among parents of children experiencing speech delay. The research employed a qualitative approach using a case study method. The research subjects were parents of children with speech delay, selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that parenting styles across all subjects were predominantly permissive, particularly the permissive indifferent type, characterized by minimal parental involvement, supervision, and control, as well as a tendency to allow children to act without clear guidance. In addition, permissive indulgent parenting was also identified, marked by emotional involvement and fulfillment of children’s desires without consistent limits. These conditions result in insufficient and ineffective communication stimulation for children. This study highlights the importance of active parental involvement and the implementation of more structured and responsive parenting practices to support optimal language development in children.